A review of the pathogenesis of epilepsy based on the microbiota-gut-brain-axis theory - Yang, Wentao; Cui, Hua; Wang, Chaojie; Wang, Xuan; Yan, Ciai; Cheng, Weiping (Frontiers in Molecular Neuroscience, 2024)
The pathogenesis of epilepsy is related to the microbiota-gut-brain axis, but the mechanism has not been clarified. The microbiota-gut-brain axis is divided into the microbiota-gut-brain axis (upward pathways) and the brain-gut-microbiota axis (downward pathways) according to the direction of conduction. Gut microorganisms are involved in pathological and physiological processes in the human body and participate in epileptogenesis through neurological, immunological, endocrine, and metabolic pathways, as well as through the gut barrier and blood brain barrier mediated upward pathways. After epilepsy, the downward pathway mediated by the HPA axis and autonomic nerves triggers “leaky brain “and “leaky gut,” resulting in the formation of microbial structures and enterobacterial metabolites associated with epileptogenicity, re-initiating seizures via the upward pathway. Characteristic changes in microbial and metabolic pathways in the gut of epileptic patients provide new targets for clinical prevention and treatment of epilepsy through the upward pathway. Based on these changes, this review further redescribes the pathogenesis of epilepsy and provides a new direction for its prevention and treatment.